BUCKLING EXPERIMENTS OF AXIALLY COMPRESSED CIRCULAR CYLINDER WITH IMPERFECT LENGTH - Ifayefunmi, O.; M. Damanhuri, A.A.; Tan, Z.H.; Ifayefunmi, O.S. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Buckling experiment on the effect of imperfect length on the buckling load of axially compressed circular cylinder is presented in this paper. Seven cylindrical specimens with different wave number ranging from 0 to 12 were manufactured using advanced manufacturing process. Specimens were cut from 1 mm mild steel plate using waterjet machining and weld using Metal inert gas welding. During the cutting process sinusoidal waves were introduced. The magnitude of the waves is assumed to be a fraction of the axial length of the cylindrical shell structure. The ratio of axial imperfection-to-axial length of the cylinder (2A/L) was taken to be 0.1. Repeatability of experimental buckling load for two nominally identical pairs with no waves (perfect) and 12 waves (imperfect) was good. The error within each pair were: 3% and 4%. Furthermore, experimental results indicate that the imperfect length in the form of sinusoidal waves strongly affect the load carrying capacity of circular cylinder [(58.62 kN; 60.47 kN) for perfect cylinders; (32.38 kN) for cylinder with 4 waves; (20.23 kN) for cylinder with 8 waves; (28.59 kN) for cylinder with 10 waves and (30.48 kN; 31.79 kN) for cylinders with 12 waves]. Also, it was revealed that the buckling load of the cylinder reduces as the axial imperfection amplitude of the cylinder increases.